Deriving Ionospheric Sporadic E Intensity From FORMOSAT‐3/COSMIC and FY‐3C Radio Occultation Measurements - Tianyang Hu; Jia Luo; Xiaohua Xu (Space Weather)
Abstract The total electron content (TEC) profiles from the FORMOsa SATellite mission‐3/Constellation Observing System for the Meteorology, Ionosphere, and Climate (COSMIC) and the Fengyun‐3C (FY‐3C) radio occultation (RO) missions during 2006 and 2019 are used to establish the models for deriving the ionospheric sporadic E (Es) critical frequency (foEs). Smax is derived as the maximum vertical gradient of TEC disturbance, which is extracted from a RO TEC profile using the singular spectrum analysis method. Three candidate conversion models are obtained by fitting Smax with foEs observed by collocated ionosondes, and the one with the best performance, the COSMIC&FY‐3C (CF) model, is applied for deriving foEs (foEsCF) from the TEC data of the two missions jointly. For comparison, the C model, which is of similar form as the CF model while being established without using the FY‐3C data, is applied for deriving foEs (foEsC) from the COSMIC TEC data only. The validations over four independent ionosonde stations demonstrate that mean improvements of 0.11 MHz (32%) in the absolute bias and 0.24 MHz (17%) in the root mean square error are obtained by foEsCF compared with foEsC. The spatiotemporal distributions of Es intensity during 2015 and 2019, presented respectively by foEsCF and foEsC, are further compared. The CF model provides more abundant and more detailed information about Es intensity distribution, which is most distinct at high latitudes where the contribution of FY‐3C RO TEC data is significant. Our results reveal that with the aging of the COSMIC satellites, FY‐3C TEC data is a valuable supplementary RO data source for Es‐related studies.